KOMITMEN GURU SMP NEGERI KECAMATAN 2X11 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Mairika Pitrawati (Jurnal Bahana Manajemen Pendidikan, 2013)
This research aimed to describeteachers commitment to student, teachers commitment to school, teachers commitment to the task and teachers commitment in Smp Negeri Kecamatan 2 X 11Enam Lingkung Kabupaten Padang Pariaman. The population areall of teacherinSmp Negeri Kecamatan 2 X 11Enam Lingkung Kabupaten Padang Pariamanamount to 84 people and the samplesare68 people that determined based on Krejcie table. Instrument usedwas a questionnaire based on likert scale and analyzed by average score formula. The results areteachers commitmentin Smp Negeri Kecamatan 2 X 11Enam Lingkung Kabupaten Padang Pariaman is good. Key Word : komitmen guru